Two-dimensional and tubular structures of misfit compounds: Structural and electronic properties - Lorenz, Tommy; Joswig, Jan-Ole; Seifert, Gotthard (Beilstein Journal of Nanotechnology, 2014)
Misfit layer compounds are structures that consist of two sublattices differing in at least one of their lattice constants. The two different layers are stacked either an alternating or in a more complex series resulting in mono- or multi-layer misfit compounds. To date, planar and bent misfit structures, such as tubes, scrolls or nanoparticles, have been synthesized and interesting magnetic and physical properties have been observed as a result of their special structures. Based on these observations, we present an overview of such misfit systems and summarize and discuss their electronic structure as well as the interlayer bonding behaviour, which is not completely understood yet. Furthermore, a more detailed insight into the SnS–SnS2 system is given, which was the first tubular misfit compound that has been synthesized and extensively investigated.
Keywords: 2D layered materials; misfit layer compounds